Intangible Resources and Organizational Performance of Food and Beverage Manufacturing Companies in Nairobi County, Kenya - Kibui, Njeri; Kiboi, Anne; Mwangi, Elias (European Journal of Business and Strategic Management, 2023)
Purpose: This study examined the influence of intangible resources on performance in the food and beverage manufacturing firms in Nairobi County. The study further sought to examine the relationship between company reputation, organizational structure, human capital, innovation capabilities and performance among food and beverage manufacturing industry in Nairobi County. Methodology: A descriptive survey research design was adopted in the study. The target population included 45 Large-Scale food and Beverage Manufacturing Companies in Nairobi County, Kenya. The unit of analysis was the food and beverage manufacturing company whereas the unit of observation was the managers of the companies. Census sampling method was used in selecting all the respondents to participate in the study. Questionnaires was used for collecting data. A pilot study was done to determine the questionnaires' validity and reliability. The collected data was analyzed quantitatively using both descriptive and inferential statistics. Statistical Package for Social Sciences was used to summarize the descriptive data into frequencies and percentages, which were then displayed using figures, tables, and charts. Multiple regression analysis was used to examine the inferential statistics. The inferential analysis assisted in establishing the relationship between the study variables, as well as in drawing findings and making recommendations for the study. Findings: The study found that the components of intangible resources account for 44.7% of the variation in the performance of enterprises in the food and beverage industry. Additionally, company reputation, Human capital, and innovation capabilities had a positive and significant influence on the performance of food and beverage companies. Organizational structure and Performance of Food and Beverage Companies was positive but insignificantly related. Unique Contribution to Theory, Practice and Policy: Resource Based View Theory, The Global Most Admired Companies (Fortune GMAC) Model, Theory of Human Capital, Mintzberg's Five Structures Model and Schumpeter's Theory of Innovation may be used to anchor future studies in the manufacturing companies. The study recommends that management should make more investment in adopting technology and improving their production processes. Additionally, the management should focus on building the capacity of their staff members through regular and consistent training. The organizational policy may also be reviewed so as to include structures that support the overall training and development of the staff members in the company. Besides training, the policies should also be draft to provide clear ways in which the companies can be able to build and communicate their brand to consumers so as to have a better reputation which as observed in the analysis contributes significantly to the improved performance of the food and beverage companies.